Pariwisata Halal di Nusa Tenggara Barat: Implementasi dalam Kawasan Ekonomi Khusus Mandalika - Amil; Zitri, Ilham; Gushadi, Artim; Darmansyah; Subandi, Azwar (Journal of Social and Policy Issues, 2023)
The concept of halal tourism for the Provincial Government of West Nusa Tenggara is to increase cultural values ​​with an Islamic identity, which is considered  a manifestation of local wisdom. The Mandalika Special Economic Zone is a popular tourist site that attracts both domestic and international visitors. The establishment of the Mandalika circuit, designed to facilitate the hosting of the MotoGP race as a globally renowned event, is expected to significantly enhance international tourism by attracting a larger number of foreign visitors. As a result of this competition, it is expected that a significant number of hotels and restaurants will be constructed in the vicinity. Nevertheless, it is important to note that the establishment in question offers not only halal food and beverages, but also non-halal options. The primary objective of this study is to investigate the strategies for the successful implementation of Halal Tourism inside the Mandalika Special Economic Zone, located in the Central Lombok Regency. The approach that researchers employed in this study is qualitative. The data collection techniques used are interviews, observation, and documentation. The results of the research show that halal tourism standards are still ambiguous, so there are still many people who do not understand the standards themselves. This is due to the lack of socialization from related agencies or organizations, giving rise to misperceptions of the concept of halal tourism itself. The policies implemented by the provincial government have not been implemented optimally. This is evident from the halal team, which has not yet been formed by the Provincial Tourism Office. The state of the population in West Nusa Tenggara, particularly in Central Lombok Regency, is conducive to the implementation of the halal tourist concept. The Kuta Mandalika region offers a favorable environment for Muslim tourists, ensuring their comfort and convenience throughout their vacation.